The relationship of vitamin D deficiency and childhood diarrhea: a systematic review and meta-analysis - Glen Lazarus; I Gusti Ngurah Sanjaya Putra; Michelle Clarissa Junaidi; Jessica Sylvania Oswari; Hanifah Oswari (BMC, 2024)
Abstract Introduction Vitamin D deficiency may increase the risk of childhood diarrhea. We aim to carry out a review and meta-analysis of the evidence relating vitamin D insufficiency to childhood diarrhea. Methods We searched PubMed, Ovid, Scopus, and Cochrane Library (from inception to August 2022), then independently reviewed the eligibility, and read full-text reviews for selected articles. Keywords used were 'vitamin D', '25-hydroxyvitamin D', 'vitamin D deficiency', 'diarrhea', 'gastroenteritis', 'children', and 'pediatric'. The search was limited to studies only in English and with available full-text. Year limitation was not applied in our search. Unpublished trials, dissertations, preliminary reports, conference abstracts, and repositories were excluded from the study. Newcastle-Ottawa Scale was used as the risk of bias assessment tool. Meta-analysis using the random-effects model was done. Results Out of 5,565 articles, 12 articles were included in our systematic review, however only 7 articles were eligible for meta-analysis. Meta-analysis showed a statistically significant association between vitamin D deficiency and diarrhea in children in developing countries (OR = 1.79; 95% CI = 1.15 to 2.80; p = 0.01). On the secondary outcome, the association of vitamin D deficiency and duration or recurrences of diarrhea are conflicting. Conclusions There is an association between vitamin D deficiency and the prevalence of diarrhea. Future studies should evaluate the causal association, the impact of vitamin D deficiency on the severity of diarrhea, and whether vitamin D deficiency treatments affects the prevalence of diarrhea.